LC-MS/MS-BASED QUANTITATIVE PROFILING OF PAPAIN ENZYME IN CARICA PAPAYA L.: METHOD DEVELOPMENT AND VALIDATION - C., CHANDAN; AGALAVE, RUSHIKESH SHIVAJI; TYAGI, TANIYA; SINGH, ADITYA KUMAR; J., RAMESH; KUMAR G., PHANI; B. V., SUSHMA; M. R., JEYAPRAKASH (International Journal of Applied Pharmaceutics, 2024)
Objective: To develop and validate a sensitive Liquid Chromatography-Tandem Mass Spectrometry (LC-MS/MS) method for quantifying the Papain enzyme in Carica papaya L. plant extracts. Methods: As an internal standard (IS), Papain was procured. A gradient-based LC-MS/MS method was developed using the Quasar C18, 150 mm × 2.1 mm, 3 µm column; the drug separation was accomplished using a gradient elution mode with a mobile phase consisting of 0.2% formic acid in water (A) and a 98:2% ratio of formic acid in acetonitrile (B). The mobile phase was injected with a volume of 10 µl at a flow rate of 0.5 ml/min. Results: Matrix-matched calibration adhering to SANCO guidelines was employed for accurate quantification, covering a concentration range of 1 to 2000 ng/ml. The method's selectivity and linearity were confirmed with an R2 correlation value of 0.990. Limits of detection (LOD) and quantification (LOQ) were determined as 170.5 ng/ml and 516.8 ng/ml, respectively. The developed LC-MS/MS method demonstrated robust analytical performance, providing a solid basis for quantifying Papain enzyme levels in Carica papaya L. plant extracts. The matrix-matched calibration approach, with a well-defined standard calibration curve, showcased the method's selectivity and linearity. The LOD and LOQ values further underscored the method's sensitivity. Conclusion: This study successfully establishes and validates a gradient-based LC-MS/MS method for accurate quantification of Papain enzyme levels in Carica papaya L. plant extracts. The demonstrated precision, accuracy, and sensitivity support the reliability of this analytical approach, offering a valuable tool for future investigations into the biological effects of Papain.